PENGARUH GAYA KEPEMIMPINAN GURU PENDIDIKAN JASMANI DAN MOTIVASI EKSTRINSIK TERHADAP MINAT BELAJAR PENDIDIKAN JASMANI SISWA SMPN KABUPATEN BANGGAI - Nurhikmah Nurhikmah (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The purpose of this study is to find out whether there is an influence of the leadership style of physical education teachers and extrinsic motivation on the interest in learning physical education students of SMPN Kab. Banggai. In accordance with these objectives, this study is a type of ex post facto correlation type research. The population is state-level junior high school students in Banggai district with a target population of 164 students, with a sample of 62 students. The data analysis technique uses Path Analysis. This research was conducted in Banggai District in the Middle School with a predicate. Data collection techniques used are observation, questionnaire, interview and documentation. The data analysis technique used is descriptive and to find out whether there are data that are normally distributed or not then the data normality test and data linearity are carried out. Infrential analysis is used to test the research hypothesis using path analysis (path analysis). The results showed that (1) There was a significant effect on the leadership style of physical education teachers on extrinsic motivation of 27.4%. (2) There is a significant influence on the leadership style of physical education teachers on physical education learning interest of 53.4%. (3) There is no significant effect on extrinsic motivation on physical education learning interest because the method of analyzing extrinsic motivation pathways is below the average score with the student response percentage of only 32.26% and not having empirical data support. Based on the results of the study it can be concluded that Based on the results of the research and discussion previously stated, it can be concluded that through the application of the Jigsaw type cooperative learning model on bulletproof material education lessons, it can improve student learning outcomes so that existing hypotheses can be answered.